2016
DOI: 10.1016/j.nrl.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Guía oficial de la Sociedad Española de Neurología de práctica clínica en epilepsia

Abstract: This Epilepsy CPG formulates recommendations based on explicit scientific evidence as a result of a formal and rigorous methodology, according to the current knowledge in the pre-selected areas. This paper includes the CPG chapter dedicated to emergency situations in seizures and epilepsy, which may present as a first seizure, an unfavorable outcome in a patient with known epilepsy, or status epilepticus as the most severe manifestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…El tratamiento con fármacos antiepilépticos en casos de estatus epilépticos secundarios a causa tóxico-metabólica en pacientes sin antecedentes de epilepsia o lesión orgánica estructural cerebral puede disminuirse progresivamente si el paciente queda libre de crisis tras la corrección completa de la causa subyacente. En caso de que se prevea recurrencia de la alteración metabólica, puede mantenerse el fármaco indicado a dosis mínima eficaz de forma preventiva 8 .…”
Section: Encefalopatía Hiperamoniémica Tras Cistectomía Radical Y Der...unclassified
“…El tratamiento con fármacos antiepilépticos en casos de estatus epilépticos secundarios a causa tóxico-metabólica en pacientes sin antecedentes de epilepsia o lesión orgánica estructural cerebral puede disminuirse progresivamente si el paciente queda libre de crisis tras la corrección completa de la causa subyacente. En caso de que se prevea recurrencia de la alteración metabólica, puede mantenerse el fármaco indicado a dosis mínima eficaz de forma preventiva 8 .…”
Section: Encefalopatía Hiperamoniémica Tras Cistectomía Radical Y Der...unclassified
“…En la actualidad son escasos los datos publicados en nuestro entorno sobre el manejo de las crisis en urgencias. Se han comunicado casos clínicos y recomendaciones prácticas basadas en guías clínicas en el manejo de crisis epilépticas tanto en jóvenes como en adultos [15][16][17][18][19], sin encontrar estudios que comparen ambas poblaciones en el manejo en la práctica clínica diaria [20]. Este tipo de estudios es importante para la planificación sanitaria y la mejora de la atención de patologías urgentes como la epilepsia.…”
Section: Introductionunclassified
“…Regarding cardiac arrhythmias as adverse events related to LCM, dose-dependent PR interval prolongation, atrioventricular blocks and bradycardia were described for both oral and intravenous routes of administration in the three randomized controlled trials which first led to the approval of LCM (Ben-Menachem et al, 2007;Halasz et al, 2009;Chung et al, 2010) in the post-marketing setting as the main observed arrhythmic events (Shaibani et al, 2009;Wymer et al, 2009;Krause et al, 2011;Nizam et al, 2011). Thus, some current clinical practice guidelines assume second and third-degree atrioventricular block as the unique contraindications for the use of LCM (Mercadé Cerdá et al, 2016). Other arrhythmic events have been described much less frequently in relation to the administration of LCM.…”
mentioning
confidence: 99%